KERAPUHAN EVIDENSI DALAM CIVIC LITERACY - Andri Fransiskus Gultom (Sophia Dharma: Jurnal Filsafat, Agama Hindu, dan Masyarakat, 2022)
The debate about civic literacy in philosophical discourse in Indonesia is still rare. This paper may have initiated this debate by anchoring philosophical criticism to the research of Armaidy Armawi and Raharjo in the Journal of Philosophy Vol 31, No. 1 of 2021 entitled: "Evaluation of Civic Literacy Socialization Program in the Formation of Young Citizen Ethics." The fundamental aim of this paper lies in the power to critique research that has fragile evidence in the discussion of civic literacy. This study uses qualitative methods with verstehen, trouble mapping, interpretation, and Myra Zarnowski's thought experiments. The research findings: first, the fragility of the evidence occurred in the two researchers due to experiencing the epistemological break. Second, the fragility of the two researchers' evidence is in the content of civic literacy because the evaluation of the two researchers missed by presenting lack of data so that the peak achievement in civic literacy is not directed at the well-inform citizens, but is concerned with the explanatory bias that exists in ethics. The recommendations of this study focus on civic literacy, which contains a structure on reading themes and civic values that can answer the needs of citizens. The implication is sense of the citizens engagement to realizing social justice.